2016
DOI: 10.1186/s13195-016-0200-3
|View full text |Cite
|
Sign up to set email alerts
|

A call for comparative effectiveness research to learn whether routine clinical care decisions can protect from dementia and cognitive decline

Abstract: Common diseases like diabetes, hypertension, and atrial fibrillation are probable risk factors for dementia, suggesting that their treatments may influence the risk and rate of cognitive and functional decline. Moreover, specific therapies and medications may affect long-term brain health through mechanisms that are independent of their primary indication. While surgery, benzodiazepines, and anti-cholinergic drugs may accelerate decline or even raise the risk of dementia, other medications act directly on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Observational studies are essential in assessing the link between medical treatments and long-term cognitive health [14, 63]. While randomized controlled trials (RCTs) are considered the best levels of evidence and are the only study design which can establish causality, their role in understanding the relationships between diabetes medications and cognitive outcomes is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies are essential in assessing the link between medical treatments and long-term cognitive health [14, 63]. While randomized controlled trials (RCTs) are considered the best levels of evidence and are the only study design which can establish causality, their role in understanding the relationships between diabetes medications and cognitive outcomes is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes drugs’ mechanisms of action involve multiple pathologies common to diabetes and dementia and AD, including insulin resistance and impaired glucose metabolism [13]. Thus, there is an intense interest in whether type 2 diabetes drugs can be repurposed to slow cognitive aging and reduce the risk of cognitive impairment and dementia through direct effects in the brain that are independent of their approved indications for treating high blood glucose [14]. In contrast, type 2 diabetes medications may also have detrimental effects on the brain, possibly through their tendency to cause hypoglycemic episodes [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, only narrative reviews were reported for the potential role of BPV in dementia and cognitive dysfunction [ 39 42 ]. Given the reduction in treat-to-target blood pressure level in recent guidelines [ 43 ], and uncertainty around the optimal blood pressure for brain health [ 1 ], it is imperative to clarify the role of blood pressure and its variability in relation to dementia [ 44 ]. A systematic review and meta-analysis pertaining to BPVs’ association with dementia, cognitive impairment, and cognitive function might in turn assist in the design of subsequent epidemiological studies and inform clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…From a comparative effectiveness research (CER) perspective, the “effectiveness” of an intervention in pragmatic trials refers to the extent to which it benefits the targeted population in routine circumstances, with the goal of supporting informed decision-making and improving healthcare. [ 1 3 ] By contrast, the “efficacy” of an intervention is related to the degree to which the intervention does what is intended under ideal conditions by means of an explanatory randomized controlled trial (RCT). [ 4 , 5 ] Nowadays, many investigators do not value or distinguish between these two concepts when designing and performing clinical trials.…”
Section: Introductionmentioning
confidence: 99%